The Relationship of Leadership Dtyles Towards Employees’ Creativity: Mediating Effect of Employees’ Empowerment in UAE Manufacturing Companies - Ahmad, Md Fauzi; Jumaa Alhosani, Jumaa Mohammed; Mohd Nawi, Mohd Nasrun (International Journal of Supply Chain Management, 2019)
The purpose of this study is to empirically investigate impact of transformational and transactional leadership on employees’ creativity and employee empowerment in this association. Over the past many decades, employees have become an organizing way of coordinating work within organization. This trend creates new challenges for leaders, as they are expected to improve their creativity simultaneously. This study proposes a conceptual framework for understanding leadership styles and employees’ empowerment to individual employees which would influence creativity. The conceptual framework includes employees’ empowerment and support for creativity as mediating variables in the effect of leadership styles on employees’ creativity. The study also validates the proposed conceptual framework using a second-order confirmatory factor analysis technique, namely, structural equations modeling, with the data collected from 597 followers from four e-government organizations in the UAE. The findings suggest that transformational and transactional leadership has significant positive impact on employees’ creativity. Moreover, employees’ empowerment have partial mediation effect in the relationship between leadership styles and employees’ creativity.This study contributes to the research that identifies employees’ creativity influenced by transformational and transactional leadership that can affect employee success and performance, particularly in the context of UAE-based egovernment organizations.